2016
DOI: 10.1080/20477724.2016.1222054
|View full text |Cite
|
Sign up to set email alerts
|

Leptospiral renal colonization status in asymptomatic rural population of Tiruchirapalli district, Tamilnadu, India

Abstract: Humans are known to excrete leptospires in their urine after recovery from illness and there are reports showing development of asymptomatic leptospiruria in settings of high disease transmission. In this regard, we sought to evaluate the asymptomatic renal carriage status of humans in the highly endemic region of Tiruchirapalli district, Tamilnadu, India. A total of 245 asymptomatic participants were included. Urine and blood samples were collected and the extent of leptospiral infection was characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…We considered it worthwhile to conduct PCR to complement the MAT, in view of the fact that at least two studies had presented evidence of urinary shedding of Leptospira by asymptomatic, MAT-negative individuals, using PCR to identify leptospiral DNA in urine samples. 43,44 Analyses were conducted using the method, including the primer/probe sequences, described by Stoddard et al 45 and modified to increase sensitivity as described by Galloway and Hoffmaster. 46…”
Section: Methodsmentioning
confidence: 99%
“…We considered it worthwhile to conduct PCR to complement the MAT, in view of the fact that at least two studies had presented evidence of urinary shedding of Leptospira by asymptomatic, MAT-negative individuals, using PCR to identify leptospiral DNA in urine samples. 43,44 Analyses were conducted using the method, including the primer/probe sequences, described by Stoddard et al 45 and modified to increase sensitivity as described by Galloway and Hoffmaster. 46…”
Section: Methodsmentioning
confidence: 99%
“…In Tamil Nadu, India, positive urine leptospira DNA was identified from 52.7% (129 of 245) asymptomatic participants. Serological results showed that 20.4% (50 of 245) of persons with urine DNA positivity were even negative for MAT indicating that deficient immunity may allow the persistence of carrier status [33]. In Nicaragua, after a major outbreak of leptospirosis in 1995, 85 out of 566 (15.0%) persons were found to be seropositive by immunoglobulin M enzyme-linked immunosorbent assay, in which only 25 (29.4%) reported having a febrile illness during the preceding 2 months; the remaining 60 (70.6%) had asymptomatic infection [34].…”
Section: Leptospirosis Chronic Carrier and Ckdmentioning
confidence: 99%
“…In general, it is accepted that humans can excrete Leptospira for weeks to months after an infection 30 ; however, a recent study in the Peruvian Amazon found that asymptomatic individuals without serological evidence of recent exposure were shedding either pathogenic or intermediately pathogenic Leptospira in their urine 31 . Another study in India used PCR to find that Leptospira was excreted in the urine by 30.2% of the asymptomatic individuals investigated 32 . It is not known whether the excretion of Leptospira in urine is a characteristic of asymptomatic leptospirosis, and we did not assess the excretion of Leptospira in our subjects.…”
Section: Discussionmentioning
confidence: 99%